Placenta previa: maternal and fetal outcome in a tertiary care institute - Pravallika, Bammidi Padma; Rao, Bhushan; Kakariya, Bhavna; Chaudhari, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Placenta previa (PP) is a serious health disorder, which leads to higher level of foetal-maternal morbidity and mortality. In this study, we evaluated maternal and fetal outcome due to PP in tertiary care institute. This research was a prospective and observational study. Among 8311 numbers of deliveries, 96 patients were presented PP admitted in Department of Obstetrics and Gynaecology, Shri Bhausaheb Hire Government Medical College, Dhule, Maharashtra, India. The study period was June 2021 to May 2022. All patients were informed and taken written informed consents. After the clinical assessment, the diagnosis was confirmed for PP. The parameters viz. age, parity, GA, previous delivery, PV bleeding, PP types, mode of delivery, intraoperative interventions, morbidity and mortality of mothers and neonatal outcomes were recorded. Our study found PP rate of about 1.15% and the prevalent age group was maximum 25-29 years. Maximum mothers were multigravida and GA was maximum>37 weeks recorded. 19 babies were observed early neonatal death. More the prevalence of PP lead to high resources utilization and risk of maternal and fetal morbidity and mortality. PP prevention can be achieved by better spacing in between pregnancies, antenatal registration of all pregnant women, routine check-up, routine use of USG in pregnancy and early referral of high-risk pregnant women to tertiary care centres.